Kajian Neoropsikology: Strategi Mnemonic Untuk Meningkatkan Kinerja Memori Dalam Pembelajaran di Sekolah Dasar - Nur Rohmah Nilam Sari; Mochamad Nursalim; Diana Rahmasari (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Human memory has a large capacity and unlimited capabilities. Humans use memory to store information important for survival. Mnemonics is a strategy to improve memory performance by encoding information with associations between new information and previously learned information in long-term memory. This research uses a qualitative research method, the Systematic Literature Review (SLR) model with the PRISMA approach with stages Identification, Screening, Eligibility, Included. Identification of literature review data was taken from publish or perish, Google Scholar, Researchgate, and ScienceDirect and 141 articles were obtained which were searched based on keywords, then in second selection they were selected based on more sensitive issues and 19 learning articles were obtained using mnemonic strategies. In the 3rd stage of selection, a study was carried out on the methodology and research results by 2 reviewers so that appropriate articles were obtained and in accordance with the SLR protocol. There were 5 relevant articles containing the issue of neuropsychological studies of learning with memory strategies that can be applied to education in elementary schools. From the results of the analysis, it was found that mnemonics are a fun learning approach strategy with a high success rate and are able to strengthen retention in long-term memory. Menmonic also improves memory performance in the part of the brain Pre Frontal Cortex.